Genetic variability studies of a novel health promoting leafy vegetable Rucola (Eruca sativa) (Bangladesh Journal of Agriculture, 2023)
Rucola is one of the important leafy vegetables of the ‘Brassicaceae’ family which is commonly consumed as raw salad. Seven rocula genotypes were evaluated during Rabi season 2021-2022 at the experimental farm of Sher-e-Bangla Agricultural University (SAU), Dhaka for genetic variability analysis and were compared with mustard genotype. The results showed that the genotypes were significantly variable for the studied traits. The phenotypic variances and phenotypic coefficient of variations were higher than genotypic variances and genotypic coefficient of variations suggesting the environmental effects on the phenotypic expression of those traits. The high heritability was observed for all the traits except the number of leaves per plant (51.24). Fresh yield per plant showed a significant positive genotypic correlation with number of leaves per plant (0.986) and number of siliquae per plant (0.845) while a significant phenotypic correlation with days to 50% flowering (0.466), plant height (0.473), number of leaves per plant (0.705), leaf length (0.547), days to maturity (0.405) and number of siliquae per plant (0.797). Moreover, seed yield per plant had significant positive correlation with thousand seed weight (0.971) while a non-significant positive correlation with leaf breadth (0.258), number of siliquae per plant (0.030), siliquae length (0.314) and pedicel length (0.168) at both genotypic and phenotypic levels. The results suggest that rucola can be cultivated in the agro-climatic condition of Bangladesh and needs for further genetic improvement of this health promoting crop. This is also the first scientific report of rucola cultivation in Bangladesh.Bangladesh J. Agri. 2022, 47(2): 53-63